Mapping properties to monitor forests: Landholder response to a large environmental registration program in the Brazilian Amazon. (30th November 2016) - L'Roe, Jessica; Rausch, Lisa; Munger, Jacob; Gibbs, Holly K.
Highlights: We evaluate the effect of an environmental land registry on landholder behavior. Registration decreased deforestation for one size-class of landholdings. This group experienced a unique set of incentives from interacting land policies. Some registrants declared boundaries strategically to fall under policy thresholds. Securing land claims may motivate local responses to the environmental registry. Abstract: Across the tropics, development banks and conservation donors are investing millions in property mapping and registration projects to improve accountability for deforestation. An evaluation of the effectiveness and accuracy of existing environmental registries is crucial to assure the success of future efforts. This study presents an evaluation of deforestation and registration behavior in response to one of the largest of these property registration programs to date — the Rural Environmental Registry (CAR) in the Amazonian state of Pará. From late 2007 to 2013, approximately 100, 000 properties covering 30 million hectares of self-declared claims were entered in this digital registry. We used fixed effects regression models and property level data to assess how registration influenced deforestation on different sizes of properties. Registration had little impact on deforestation behavior, with the exception of a significant reduction on "smallholder" properties in the size range of 100–300 ha. We link this reduction to interacting incentives from forest protection and land regularization policies and suggest that desire to strengthen land claims motivates these landholders' response to the environmental registry. We also present evidence that some landholders may be registering incomplete or inaccurate parcels into the self-declared system to strategically benefit from policy incentives. Our results for smallholder properties indicate that environmental registries may have potential to facilitate reductions in deforestation if combined with a favorable combination of incentives. However, in places where land tenure is still being negotiated, the utility of environmental registries for forest policy enforcement and research may be limited without ongoing investment to resolve uncertainty around land claims.